Integrating CRTWC's Anchor Competencies Framework into an ESP Syllabus for Fostering Social Emotional Learning Skills - Mythiri, B.; Karthika, V. K. (Journal of Engineering Education Transformations, 2025)
The Centre for Reaching & Teaching the Whole Child (CRTWC) worked on integrating the seven anchor competencies such as building trusting relationships, facilitating self-reflection, fostering growth mindset, cultivating perseverance, creating community, promoting collaborative learning, and responding constructively across differences with the social-emotional competencies. The ‘CRTWC’s Anchor Competencies Framework’ was developed with a culturally responsive teaching lens (Markowitz & Bouffard, 2020 ) based on the CASEL’s (Collaborative for Academic, Social and Emotional Intelligence) five social, emotional competencies such as self-awareness, self-management, social awareness, relationship skills, and responsible decision making. The present study, situated in an English for Specific Purposes (ESP) classroom of 120 engineering students at NIT Trichy, India, explores the need for Social Emotional Learning (SEL) and how language learning activities designed based on CRTWC’s anchor competencies framework and corresponding teacher moves assist in developing the SEL skills of the learners. Learners’ assignments, their self-reflection reports, and the learner-feedback obtained through a 7 week-intervention, served as the primary data. Teacher-researchers’ diary entries were also analysed to corroborate the findings. Visual narrative analysis and narrative thematic analysis were employed to explicate the data. Findings of the study suggested the importance of SEL skills and the ways in which these skills could be incorporated into the existing ESP course-plan. The study also underscored that those activities designed within the anchor competencies framework along with the corresponding teacher moves, support the SEL of the learners even in an online classroom environment.